2002
DOI: 10.1073/pnas.142313799
|View full text |Cite
|
Sign up to set email alerts
|

Modulating influence on HIV/AIDS by interactingRANTESgene variants

Abstract: RANTES (regulated on activation normal T cell expressed and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
182
4
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(205 citation statements)
references
References 37 publications
12
182
4
4
Order By: Relevance
“…In the context of haplotypes involving these SNPs, the -28G/-403G haplotype has been associated with near-fatal asthma in Chinese children [23]. In addition, the -403A/-28G haplotype has been shown to be associated with a slower rate of CD4+ T-cell depletion in HIV-1-infected Japanese subjects [1], and haplotypes that included 375C displayed a strong dominant association with rapid progression to AIDS among HIV-1-infected individuals in African-American, European-American and combined cohorts [21]. Therefore, the present authors believe that the genetic association observed in the present study is due to the functional consequences that these functional SNPs have on CCL5 transcriptional activity, although the possibility that they act as markers of another important genetic abnormality without themselves being functionally relevant cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the context of haplotypes involving these SNPs, the -28G/-403G haplotype has been associated with near-fatal asthma in Chinese children [23]. In addition, the -403A/-28G haplotype has been shown to be associated with a slower rate of CD4+ T-cell depletion in HIV-1-infected Japanese subjects [1], and haplotypes that included 375C displayed a strong dominant association with rapid progression to AIDS among HIV-1-infected individuals in African-American, European-American and combined cohorts [21]. Therefore, the present authors believe that the genetic association observed in the present study is due to the functional consequences that these functional SNPs have on CCL5 transcriptional activity, although the possibility that they act as markers of another important genetic abnormality without themselves being functionally relevant cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%
“…Three common SNPs of functional relevance have been identified in the regulatory region of CCL5 (-403G.A, -28C.G and 375T.C); these three SNPs influence transcriptional activity in vitro and subsequent CCL5 expression in human cell lines [1,20,21]. These SNPs were associated with increased levels of CCL5 [2,22], as well as increased blood eosinophil counts [23].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activity of two promoter SNPs (rs2280788: À28*C/G and rs2107538: À403*G/A) and an SNP in intron 1 (rs2280789: Int1.1*T/C) has been investigated. 7,21,22 An et al 22 showed that transcription activity was mainly regulated by the Int1.1 genotype. Int1.1*C allele strongly downregulates the transcriptional activity of RANTES, whereas the À403*G/A SNP has no effect on transcription and the À28*G allele shows a modest upregulation.…”
Section: Association Of Rantes With T1dmentioning
confidence: 99%
“…Int1.1*C allele strongly downregulates the transcriptional activity of RANTES, whereas the À403*G/A SNP has no effect on transcription and the À28*G allele shows a modest upregulation. 22 We have investigated the SNP rs2306630, which, according to the HAPMAP data, is a perfect proxy of the Int1.1 SNP (where the Int1.1*C allele could be tagged by the rs2306630*G allele and the Int1.1*T allele corresponds to the rs2306630*A allele). We observed that the haplotype 2, which is tagged by the rs2306630*A allele, is associated with a lower protein level of RANTES.…”
Section: Association Of Rantes With T1dmentioning
confidence: 99%
See 1 more Smart Citation